2013
DOI: 10.2478/aoas-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the osteopontin gene and level of its expression in the reproductive tract of sows / Polimorfizm w genie osteopontyny i poziom jej ekspresji w układzie rozrodczym loch

Abstract: The aim of the study was to find osteopontin gene (OPN) polymorphisms as potential mutations affecting the expression level of genes in the ovaries, uterus and oviduct of sows. The material consisted of 71 F1 sows (Polish Large White × Polish Landrace). In the first stage several polymorphisms in the promoter region, intron 6, exon 6 and 7 of the OPN gene were found. The parameters estimated were the frequency of alleles and genotypes, observed heterozygosity and gene diversity, PIC, and chi2 factors. Chi2 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Zhao et al [60] reported that allele B of the FSHB gene increased (on average) the number of piglets per litter by 1.5 (in all the analyzed litters), and accordingly they proposed that FSHB gene polymorphism could be used in marker-assisted selection (MAS). Similarly, a positive effect of allele B on the litter size in a Tibetan breed of swine was observed by Liu et al [45], whereas Wang et al [43] found that Large White sows with genotype BB had an average of 1.13 piglets more (in the 2nd litter) than females with genotype AB. The result was confirmed in a more recent study by Pang et al [61], who estimated the additive effect of allele B of the FSHB gene on the litter size in Large White sows at 0.48 (for TNB) and 0.65 (for NBA) piglets per litter (p<0.01).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Zhao et al [60] reported that allele B of the FSHB gene increased (on average) the number of piglets per litter by 1.5 (in all the analyzed litters), and accordingly they proposed that FSHB gene polymorphism could be used in marker-assisted selection (MAS). Similarly, a positive effect of allele B on the litter size in a Tibetan breed of swine was observed by Liu et al [45], whereas Wang et al [43] found that Large White sows with genotype BB had an average of 1.13 piglets more (in the 2nd litter) than females with genotype AB. The result was confirmed in a more recent study by Pang et al [61], who estimated the additive effect of allele B of the FSHB gene on the litter size in Large White sows at 0.48 (for TNB) and 0.65 (for NBA) piglets per litter (p<0.01).…”
Section: Discussionmentioning
confidence: 65%
“…By contrast, other studies did not show any associations between the SNP in the RBP4 gene (g.447G>C) and the number of piglets per litter [9,[42][43]. No effect of this genotype on litter size has been reported in German Large White [37] and Polish Large White, Landrace and commercial line 990 pigs [44] as well as in Chinese [45] and local Indian breeds [46].…”
Section: Discussionmentioning
confidence: 80%